Cartera vencida de la Cooperativa de Ahorro y Crédito San Antonio de la ciudad de Vinces, provincia de Los Ríos en el periodo 2023. - Nivela León, Deiner Steven (2024)
This case study was developed in the San Antonio Savings and Credit Cooperative in the city of Vinces, Los Ríos province, which faces challenges related to the management of the overdue credit portfolio. The primary objective is to examine the overdue portfolio and to be able to determine, through financial indicators, the level of delinquency with its partners. A study was conducted with a mixed approach that brings together both qualitative and quantitative methods, this includes an interview with the manager and the analysis of the cooperative's financial information during the periods 2022 - 2023. The largest proportion of the overdue portfolio corresponds to the microcredit portfolio, of which for the year 2022, representing 74.53% of the total credit portfolio, while for the year 2023 it increased with a percentage of 71.31%, evidencing a relevant long-term accumulation, in addition to verifying the effect of the overdue portfolio, the liquidity indicator was used, which for the year 2022 a liquidity was obtained with 23% and in 2023 with 6.3% facing a risk for the cooperative. A good provision for bad debts was observed with a coverage ratio of 2.64 for the period 2023, which despite its decrease, the results were favourable, so good provisions must continue to be maintained to cover future losses.